2021
DOI: 10.1021/acs.jpcb.1c03283
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Insights into Protein Adsorption on Supramolecular Assemblies of π-Amphiphiles

Abstract: Nonspecific adsorption of proteins on the surface of nanocarriers plays a critical role in their cellular uptake and other biological functions. This article reports vesicular assemblies of two πamphiphiles (NDI-1 and NDI-2) and thermodynamic aspects of their interaction with bovine serum albumin (BSA). Both contain a hydrophobic naphthalene-diimide (NDI) core and two oligo-oxyethylene (OE) wedges but differ by the presence of the hydrazide group in NDI-1. NDI-2 exhibits a constricted π-stacking and enthalpy-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Understanding the fundamental aspects of such interactions is of close relevance to biological applications of any new nanocarriers in general because when administered in a physiological system, such issues greatly impact their cellular uptake and other biological functions. While PEG-decorated systems have been extensively studied in this context, a newly introduced system, such as PU-6b with much shorter OEG chains exhibited at the surface, are less known Figure shows the ITC plot of the interaction of BSA with PU-6b at 22 °C (just around cloud point).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Understanding the fundamental aspects of such interactions is of close relevance to biological applications of any new nanocarriers in general because when administered in a physiological system, such issues greatly impact their cellular uptake and other biological functions. While PEG-decorated systems have been extensively studied in this context, a newly introduced system, such as PU-6b with much shorter OEG chains exhibited at the surface, are less known Figure shows the ITC plot of the interaction of BSA with PU-6b at 22 °C (just around cloud point).…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by these results, we further examined nonspecific adsorption of a model serum protein BSA on the OEG-occupied surface of the PU-6b capsule. First, it was probed by DLS study (Figure S15), which showed an increase in the D h of PU-6b from 300 to 470 nm in the presence of BSA, indicating the adsorption of the protein on the surface of the aggregates . We further examined the detailed thermodynamic aspects of such nonspecific protein adsorption by ITC studies (Figures and S16) and correlated the results with the LCST.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations